PENGARUH AKSES SITUS PORNO DAN TEMAN SEBAYA TERHADAP PERILAKU SEKSUAL REMAJA DI SMA YAYASAN PERGURUAN KESATRIA MEDAN TAHUN 2014 - uci kirana; Yusniwarti Yusad; Erna Mutiara (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSRACT Teenagers is a potency in the continuing development of a nation. The existence of the various development efforts carried out, caused changes in the life of teenagers. This happens due to an imbalance in the development efforts made against teenagers, giving rise to problems for the construction it self. One of the effects of the imbalance in development is the occurrence of a fundamental change in the attitudes and sexual behaviour among teenagers. Many of the factors that led to a change in attitude and sexual behavior among teenagers, among others, the influence of access porn sites and peers. This research aimed to know the influence of access porn sites and peer group on teenagers sexual behavior in SMA Yayasan Perguruan Kesatria Medan. Type of this research is a descriptive analytic survey with cross sectional approach. The population of this research were all of students at SMA Yayasan Perguruan Kesatria Medan who have been dating, by using totally 107 students were being sample. This study uses multivariate analysis. The results of this research showed that teenagers sexual behavior in the severe category numbered 32 students (29.9%). Variables related to teenagers sexual behavior is an access porn sites (p = 0.042) and adaptation to the peer group (p = 0.034). The results of research using multiple logistic regression test shows that the most influential variables on teenagers sexual behavior is adaptation with peer group, with the regression coefficient β= 1.324. Based on research result suggested to the schools and parents to provide appropriate information and guidance to teenagers about sex education and reproductive health. To teenagers should be more wise in using the internet as a medium to increase knowledge in order to be more useful. Keywords: Free Porn Sites, Peer group, Teenagers Sexual Behavior